What factors mediate the relationship between global self-worth and weight and shape concerns?. (April 2016) - Murphy, Edel; Dooley, Barbara; Menton, Aoife; Dolphin, Louise
Abstract: The primary aim of this study was to investigate whether the relationship between global self-worth and weight concerns and global self-worth and shape concerns was mediated by pertinent body image factors, while controlling for gender and estimated BMI. Participants were 775 adolescents (56% male) aged 12–18 years ( M  = 14.6; SD  = 1.50). Mediation analysis revealed a direct and a mediated effect between global self-worth and two body image models: 1) weight concerns and 2) shape concerns. The strongest mediators in both models were physical appearance, restrained eating, and depression. Partial mediation was observed for both models, indicating that body image factors which span cognitive, affective, and behavioral constructs, explain the association between global self-worth and weight and shape concerns. Implications for future research, weight and shape concern prevention and global self-worth enhancement programs are discussed. Highlights: Global self-worth was directly related to weight and shape concerns. Proposed mediators explained the direct effect between self-worth and body image. Gender was not observed to moderate the mediated models.